The Novel Nutraceutical KJS018A Prevents Hepatocarcinogenesis Promoted by Inflammation. (1st August 2018) - Huynh, Do Luong; Chandimali, Nisansala; Zhang, Jiao Jiao; Kim, Nameun; Park, Yang Ho; Kwon, Taeho; Jeong, Dong Kee
Abstract : Inflammation is tightly associated with carcinogenesis at both the initiation and development of tumor. Many reports indicated that Cox-2 substantially contributes to inflammation and tumorigenesis. The novel nutraceutical KJS018A (BRM270 Function Enhanced Products) is the extract mixture from 8 herbal plants, which have been used to inhibit cancers and inflammation. The aim of the present study is to examine the inhibitory effects of KJS018A mixture to hepatocarcinogenesis and inflammation. The results showed that KJS018A significantly inhibited the proliferation of hepatic malignant cells and downregulated levels of IL-6 and Cox-2. Furthermore, KJS018A diminished the effect of PMA, an inflammatory inducer via IL-6/STAT3/Cox-2 pathway. Furthermore, KJS018A suppressed metastatic traits of hepatic malignant cells via downregulating Twist, N-cadherin, and MMP-9 while restoring E-cadherin expression. KJS018A also restrained tumor growth and levels of IL-6 and Cox-2 in immunohistochemistry staining. Taken together, these data suggest potential application of KJS018A in prevention of hepatocarcinogenesis promoted by inflammation.